Predicting Overburden-Induced Failure Height of Large Mining Face in Shallow Coal Seam Based on Half-Plane Theory - Shuai Di (Shock and Vibration)
Research on the overburden-induced failure height in large mining faces is important for solving the problems of sand rupture and water permeability when mining in shallow depth. In order to solve the safety and high-efficiency mining problems, this study used the 7 m-high face #52306 of the Daliuta mine as the object of research for theoretical analysis and field measurements. The results show that the traditional empirical formula is not suitable for predicting overburden on three zones of the large mining face in shallow depth. We use elastic half-plane theory to establish a mechanical model to calculate overburden-induced stress and analyze the law of transmission of abutment pressure in the overburden. We then use maximum shear stress theory to develop a method to predict the height of the overburden in the “three zones” of the mining face based on the law of change in the shear stress. According to the characteristic whereby shear stress at the rear of the working face increases first and then decreases, the area where the shear stress was greater than zero was defined as the zone of water conduction-induced fracture, the area where the shear stress increased was identified as the zone of collapse, and the area where the shear stress decreased was defined as the fracture zone. A comparison of the theoretically calculated values with empirically measured data showed that the relative error was controlled to within 6%, verifying the reliability of the proposed method. The results here can provide useful information for the efficient and environmentally friendly mining of shallow coal seams.